2011
DOI: 10.1002/micr.20925
|View full text |Cite
|
Sign up to set email alerts
|

Nerve growth factor combined with an epineural conduit for bridging a short nerve gap (10 mm). A study in rabbits

Abstract: The purpose of this study was to evaluate the effect of direct administration of nerve growth factor (NGF) into an epineural conduit across a short nerve gap (10 mm) in a rabbit sciatic nerve model. The animals were divided into two groups. In group 1, n = 6, a 10-mm defect was created in the sciatic nerve and bridged with an epineural flap. A dose of 1 μg of NGF was locally administered daily for the first 21 days. NGF administration was made inside the epineural flap using a silicone reservoir connected to a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
18
0

Year Published

2012
2012
2018
2018

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 18 publications
(19 citation statements)
references
References 37 publications
1
18
0
Order By: Relevance
“…We have also confirmed that epineural conduit supported with BMSC significantly improved myelin thickness and the number of large diameter fibers within the regenerating axons at 12 weeks post‐repair compared to the autograft control. This study is in line with observations of Barmpitsioti et al (), who reported enhanced nerve regeneration using epineural tubes supported with nerve growth factor in the rabbit model of sciatic nerve repair.…”
Section: Discussionsupporting
confidence: 93%
“…We have also confirmed that epineural conduit supported with BMSC significantly improved myelin thickness and the number of large diameter fibers within the regenerating axons at 12 weeks post‐repair compared to the autograft control. This study is in line with observations of Barmpitsioti et al (), who reported enhanced nerve regeneration using epineural tubes supported with nerve growth factor in the rabbit model of sciatic nerve repair.…”
Section: Discussionsupporting
confidence: 93%
“…Biological and synthetic nerve conduits have had some success in early clinical studies on reconstruction of nerve defects in the hand . The effectiveness of nerve regeneration could potentially be increased by using these nerve conduits as scaffolds for delivery of Schwann cells, stem cells and neurotropic factors or extracellular matrix proteins . Currently, the repair is made by using sutures to fix the graft or the tube to the injured nerve.…”
Section: Discussionmentioning
confidence: 99%
“…Different conduits have been used to bridge nerve gaps, using biological and nonbiological tubular nerve guides. The biodegradable polymers have the advantage of avoiding a second surgery to remove them, and also preserve a healthy nerve …”
mentioning
confidence: 99%
“…The model of 10 mm sciatic nerve gap used successfully for assess nerve repair in several studies was chosen to assess peripheral nerve regeneration in this study [20][21][22][23] and this nerve gap was bridged with silicone tube or ANG.…”
Section: Operative Proceduresmentioning
confidence: 99%